Law in a changing society - Friedmann, Wolfgang ([Harmondsworth, Eng.] : Penguin Books, 1964)
The book basic theme is the dual function of the legal order as a reactor to and increasingly as initiator of social change.
Bibliography: p. [453]-465.
gp. 22/01/2019
Loans
Keywords: Sociological jurisprudence; Law; Law reform; Social change